New Design of 60 GHz MIMO 2x4 Patch Rectangular Antenna Array for Wireless Gigabit (Wi-Gig) Application - Rahayu, Yusnita (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
Nowadays, most antenna researchers over the world are focusing on the design of the antenna for the fifth generation (5G) application (indoor and outdoor). High intensive research on 60 GHz antenna for high data rate indoor communication is becoming a trending topic. The high propagation loss at this band is the most challenging. The antenna needs to have higher gain to overcome the loss. Such antenna designs have been proposed recently. This paper, a new MIMO 2x4 patch rectangular antenna operating at 60 GHz is designed for Wi-Gig application. The rectangular patch antenna has 1.75 mm x 1.54 mm of size, printed on Rogers Duroid RT 5880 substrate, the dielectric constant of 2.20 and loss tangent of 0,0009. The antenna was designed and simulated using CST simulation software. The simulated return loss showed a very consistent characteristic. The return loss reached −30 dB at 60 GHz. The broad bandwidth obtained is 4.3 GHz concerning -10 dB. The omnidirectional radiation pattern with 13.4 dBi of gain is obtained. This antenna meets the Wi-Gig requirement.